Protection of the information and observance of access rights in it is hardware-programnom the complex <ACCESS> - Чиж, Александр Иванович (Eastern-European Journal of Enterprise Technologies, 2011)
The opportunity of creation and use of the program of protection of the information and differentiation of access rights is investigated at operation of a hardware-software complex <ACCESS>